High Albumin Level Is Associated With Regression of Glucose Metabolism Disorders Upon Resolution of Acute Liver Inflammation in Hepatitis B-Related Cirrhosis - Tian, Caiyun; Zhu, Yanping; Liu, Yujuan; Hu, Han; Cheng, Qijiao; Yang, Fangwan; Pei, Lingqi; Zhou, Yihong; Li, Ying; Lin, Shide (Frontiers in Cellular and Infection Microbiology, 2022)
Background and aim: To investigate the short-term dynamic changes and the factors associated with regression of glucose metabolism disorders in patients with hepatitis flare of chronic hepatitis B virus (HBV) infection. Methods: 118 patients with severe hepatitis flare of chronic HBV infection were prospectively included in this study. Oral glucose tolerance test was performed on admission and during follow-up to evaluate dynamic changes in glucose metabolism disorders. The factors associated with regression of glucose metabolism disorders were identified using univariate and multivariate logistic regression. Results: The prevalence of diabetes was significantly higher in 70 patients with liver cirrhosis (47.1%) than that in 48 patients without liver cirrhosis (16.8%). The prevalence of impaired glucose tolerance in patients with liver cirrhosis (35.7%) was significantly lower than that in patients without liver cirrhosis (47.8%). After a follow-up of 20.0±18.7 days, 28 of 31 (90.3%) patients without liver cirrhosis had their glucose metabolism disorders regressed. 30 of 55 (54.5%) patients with liver cirrhosis also had regression of their glucose metabolism disorders after 42.0±36.2 days. In patients with liver cirrhosis, those with regression of glucose metabolism disorders had significantly higher levels of homeostasis model assessment 2-β-cell function, albumin (ALB), and a significantly lower level of fibrosis-4 score. ALB was identified as an independent factor associated with the regression of glucose metabolism disorders in patients with liver cirrhosis. Conclusion: High ALB level is an independent factor associated with regression of glucose metabolism disorders in patients with liver cirrhosis and hepatitis flare of chronic HBV infection.